Use Of Digital Learning Documents In Islamic Religious Education In The 21st Century - Ismaniyah, Farihatul; Zainiyati, Husniyatus Salamah; Asrohah, Hanun (Yayasan Rahmat Islamiyah, 2025)
Technological developments in the 21st century have had a significant impact on the world of education, including Islamic Religious Education (PAI). The use of digital learning documents is an innovative solution to support more relevant, interactive and flexible learning. Various types of digital documents, such as e-books, interactive videos, infographics and Islamic podcasts, offer broad accessibility and support the diversification of students' learning styles. Additionally, digital documents can increase student engagement through interactive features, enrich the learning experience, and support independent learning. However, challenges such as infrastructure gaps, teacher digital literacy, and the need for content conformity with Islamic values are obstacles to its implementation. Using a literature review approach, this article analyzes the benefits of digital documents in PAI learning and formulates implementation strategies.